Dual functions of the Drosophila eyes absent gene in the eye and embryo. - Leiserson, W.M.; Benzer, S.; Bonini, N.M. (Mechanisms of Development, 1998)
In eyes absent (eya) mutants, eye progenitor cells undergo cell death early in development. Whereas the phenotype of eya1 is limited to the eye, other mutations are lethal. Genetic and molecular analysis reveals that mutations in one region of the gene cause embryonic lethality, whereas mutations throughout the gene cause defects in eye development. Mosaic analysis indicates that the eya requirement is cell autonomous. In eye-specific mutants, expression in the eye disc is lacking while embryonic expression is normal. Both the type I and type II transcripts are expressed in the developing eye, and expression of either can rescue the eye phenotype. These data indicate a specific requirement for eya function in eye progenitor cells that is normally fulfilled by both transcripts.